Entre o lícito e o ilícito: a dinâmica do roubo de cargas e suas zonas cinzentas - Leonardo José Ostronoff; Fernando Salla (Ciências Sociais Unisinos)
The article discusses property crime in the form of cargo theft. It analyzes the criminal dynamics in which it is inserted, as well as the institutional and business responses to control it. It addresses cargo theft as an expression of gray areas that are established between legal and illegal, between public and private. It describes the two main types of this crime: those committed “on the spot” and specialized ones. It addresses the participation of organized criminal groups in this type of crime. It also discusses the relevant figure in this criminal modality, which is the receiver. The central argument of the article is that the crime of cargo theft because it affects the interests of economic corporations, promotes an articulation of these with the public sectors, especially the police, with a view to their containment. The Military Intervention in Public Security in Rio de Janeiro, in 2018, expresses this mobilization of economic corporations in government spheres in order to promote a wide-ranging action not only police, but also political. The methodology used was that of documentary research with the police and armed forces; interviews with civilian and military police, officers of the high command of the armed forces, businessmen, company executives and persons detained for the crime of cargo theft.